Теоретические аспекты инновационной деятельности современного предприятия - Merenkova I. A. (Priority directions of science and education development, 2017)
This article is dedicated to the study of the significance of innovation for the successful functioning of enterprises in modern market conditions. A classification of innovations in various areas of enterprise activity. The factors influencing the susceptibility to innovations, and identifies conditions contributing to the search for new ways of development.
Keywords: инновационная деятельность; инновационный проект; innovation; management innovation; инновации на предприятии; классификация инноваций; совершенствование производства; менеджмент в сфере инноваций; innovation enterprise; classification of innovations; innovative project; production improvement